2022
DOI: 10.34190/ejel.20.3.2286
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp as a tool for Building a Learning Community

Abstract: WhatsApp groups are considered useful for creating and supporting virtual communities. This mixed method case study explores the patterns that emerged when we used WhatsApp to create a community of learning during the multimodal presentation of a postgraduate course in research proposal writing. Three questions drive the study: (1) What kinds of messages were sent? (2) Who participated and how? (3) How did the learners experience the use of WhatsApp in support of the community of learning? Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Scholars also have indicated that CoP in social media develops knowledge management (Al-ghamdi & Alghamdi, 2015;Ekici, 2017;Li et al, 2009;Trust, 2015), collaboration (Li et al, 2009;Della & Jurberg, 2019), sense of belonging (Ekici, 2017;Li et al, 2009;Della & Jurberg, 2019), motivation (Ekici, 2017), and the ease of using social media platform (Dogoriti & Pange, 2014). Cronjé and Izak (2022) highlight the value of CoP via WhatsApp tool as it facilitates information sharing, feedback provision, and interaction among individuals with shared interests, promoting the development of autonomy skills. The researchers reiterate that using WhatsApp in education builds an influential learning community by allowing continuous discussions.…”
Section: Community Of Practice Via Whatsappmentioning
confidence: 99%
See 4 more Smart Citations
“…Scholars also have indicated that CoP in social media develops knowledge management (Al-ghamdi & Alghamdi, 2015;Ekici, 2017;Li et al, 2009;Trust, 2015), collaboration (Li et al, 2009;Della & Jurberg, 2019), sense of belonging (Ekici, 2017;Li et al, 2009;Della & Jurberg, 2019), motivation (Ekici, 2017), and the ease of using social media platform (Dogoriti & Pange, 2014). Cronjé and Izak (2022) highlight the value of CoP via WhatsApp tool as it facilitates information sharing, feedback provision, and interaction among individuals with shared interests, promoting the development of autonomy skills. The researchers reiterate that using WhatsApp in education builds an influential learning community by allowing continuous discussions.…”
Section: Community Of Practice Via Whatsappmentioning
confidence: 99%
“…They identified that online group discussion through the WhatsApp tool among visually impaired learners allowed knowledge sharing and developed collaboration, communication, and a sense of belonging. Cronjé and Izak (2022) investigated the use of WhatsApp as a platform for a CoP among postgraduate students in a research proposal writing course. They found out that most learners favoured using WhatsApp as a medium for CoP because it fosters interactions and knowledge sharing.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations